HYPOTENSIVE EFFECTS AND ACUTE TOXICITY PROPERTY OF METHANOL EXTRACT OF BAISSEA AXILLARIS HAU. LEAF ON ANIMAL MODELS - Idu, M.; Timothy, O. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The hypotensive and acute toxicity activities of methanol extract of B. axillaris leaves, obtained by Soxhlet extraction, were analyzed using animal models. The extract exhibited a dose-dependent reduction in rabbit blood pressure. Basal mean arterial pressure of 115.67±3.60 mmHg was progressively reduced to 106.22±3.13 and 69.3±2.59 mmHg by 2.5 and 20 mg kg-1 doses of extract respectively. Haematological parameters in Wister rats treated with 1, 2 and 4 g kg-1 of extract showed no significant difference (P>0.05). However, lethal dosage was obtained at 8 g kg-1. The results obtained showed that the extract has a blood pressure lowering effect.